A retrospective study of prognostic factors and treatment outcome in advanced-stage Mycosis Fungoides and Sezary Syndrome - Zhuo-fan Xu; Hongyun Chen; Yuehua Liu; Wei Zhang; Hongzhong Jin; Jie Liu (Hematology)
Background: Mycosis fungoides (MF) and Sezary Syndrome (SS) comprise over half of all Cutaneous T-cell lymphoma diagnoses. Current risk stratification is largely based on TNMB staging, few research investigated the prognostic value of clinical exams. Current systemic therapy for advanced disease includes immunomodulatory drugs, chemotherapy, and HADC inhibitors. Few clinical trials or retrospective research compared the efficacy of different drugs.Method: Here, we performed a retrospective analysis of prognostic factors and treatment outcomes of 92 patients diagnosed with MF/SS at the Peking Union Medical College Hospital from 2013-2023.Results: Cox regression analysis identified that age ≥ 50 years, WBC ≥ 8 × 109/L, serum LDH ≥ 250U/L, β2-MG ≥ 4.50 mg/L, and stage IV were associated with reduced overall survival, age ≥ 50 years, serum LDH ≥ 250U/L and stage IV were associated with reduced progression free survival. Kaplan-Meier analysis established that immunomodulatory therapy was associated with longer progression free survival.Conclusion: These results suggested new factors in predicting prognosis and selecting appropriate treatments in patients with advanced MF/SS.